Perceptions of Jewish and Israelis in Italy: Evidence from a Survey Experiment on Political Orientation - Fiore, Enea; Mancosu, Moreno; Pessina, Gianmaria (PARTECIPAZIONE E CONFLITTO, 2025)
Following the Hamas attacks of October 7, 2023, and the subsequent outbreak of another phase of the Israel-Palestine conflict, the debate on whether criticism of Israel can mask antisemitic prejudice in Western countries has intensified. This study investigates how ideology shapes perceptions of Jews and Israelis in Italy, a context historically marked by right-wing antisemitism and left-wing anti-imperialist critiques. We employ a survey experiment (n=1,119) to measure attitudes toward Jews and Israelis/Israel, to test the pop-theory that posits a "horseshoe" pattern of antisemitism - that is, antisemitic attitudes should be most prevalent at the extremes of the political spectrum and attenuated at more central positions. Contrary to expectations, our findings show no significant convergence of antisemitic attitudes at the ideological extremes. Instead, left-leaning respondents distinguish more clearly between Jews and Israelis, whereas right-leaning respondents conflate the two identities. These results highlight the mechanism that disentangles prejudice from political critique and underscore the moderating effect of ideology in shaping public opinion toward Jewish/Israeli communities.